Lecturing within the panoptic scheme of prevent in an English University. Issue 4 (2nd October 2021) - Robson, Jennifer; Hunt, Ruth
ABSTRACT: The Counter Terrorism and Security Act (CTSA) in 2015 placed responsibilities for national security on Higher Education (HE) in England with implications for lecturers' roles and responsibilities as they engage with students. The principal aim of this inquiry was to develop an understanding of lecturers' pedagogy in the context of students' academic study of Prevent in the fields of primary education and early childhood education (ECE). Panopticism was adopted as a theoretical lens to reveal the means by which the policy and structures of counter-terrorism reach into the university classroom. Subsequently, practitioner inquiry was applied as a method to examine the assumptions that underlie pedagogical decisions made by lecturers in this context. Findings from this small-scale inquiry indicate that lecturers held complex assumptions relating to both the aims of the CTSA and students' agency as learners. Such assumptions informed the way lecturers modified pedagogy in their attempts to create spaces for students to construct critical knowledges of the implications of counter-terrorism policy. Within the literature on the implications of CTSA for pedagogy in HE, this article highlights the value of practitioner inquiry as a critical tool for research into teaching and learning in this context.